SIstema de aquisição de sinal eletromiográfico (EMG) para aplicação em controle - Santos, Lizandra Meire Moreira (Universidade Federal Rural do Semi-Árido, 2017)
As not all individuals have an ability to move their arms or legs, improvements in equipment and machines that are made to facilitate or enable displacement, or another function that can be performed by capturing biosynths located in the muscles, such as pushing a chair Wheels It is due to the growing problem of reintegration of disabled people in the middle that one thinks of doing this project. The sign that one wants to use the electromyographic (EMG) is very important, used to reveal information related to the state of activation of the muscle. The places chosen to capture these were the muscles of the biceps and triceps, supporting people with simpler motor difficulties. The function of biopotentials is to measure the electromagnetic field produced by the activity of different systems of the body, through the neurons and muscles that detect them. This work aims to develop a system aimed at the welfare of people with motor needs through myoelectric signals from the movement of the arm, no intention to make these individuals independent to perform as simple tasks by day, or even play Some function in the job market. The main objective of this work is to obtain an instruction of the electromyographic signal, the biceps warnings and the triceps of an individual, to prove the ability to record the signals. This work shows the development of a myoelectric signal acquisition system. The signals are captured by cable electrodes through a biomedical instrumentation amplifier, this amplifier that accompanied a filter for a better study of the acquisition of myoelectric signal. The use of biosafety for the movement of wheelchairs and muscles is shown satisfactory in its significant amplitude verified through the oscilloscope.
Keywords: Eletromiografia; aquisição de sinais; amplificador; cadeira de rodas; electromyography; signal acquisition; amplifier; wheelchair; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA